2005
DOI: 10.1002/pola.20986
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular design via reversible addition–fragmentation chain transfer (RAFT)/xanthates (MADIX) polymerization

Abstract: Among the living radical polymerization techniques, reversible addition-fragmentation chain transfer (RAFT) and macromolecular design via the interchange of xanthates (MADIX) polymerizations appear to be the most versatile processes in terms of the reaction conditions, the variety of monomers for which polymerization can be controlled, tolerance to functionalities, and the range of polymeric architectures that can be produced. This review highlights the progress made in RAFT/MADIX polymerization since the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
1,051
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,150 publications
(1,065 citation statements)
references
References 343 publications
(722 reference statements)
9
1,051
0
5
Order By: Relevance
“…[1][2][3] It has been well-established that the topological structures and chemical composition of nonlinearshaped block copolymers can exhibit dramatic effects on the solution properties and self-assembling morphologies as compared with their linear counterpart. [4][5][6][7][8][9] It is worthy of noting that the developments of a variety of controlled radical polymerization techniques 10 such as atom transfer radical polymerization (ATRP), [11][12][13] reversible addition-fragmentation chain transfer (RAFT) polymerization, [14][15][16] and nitroxide-mediated polymerization (NMP) 17,18 have facilitated the synthesis of nonlinear-shaped polymers with varying chain architectures such as cyclic, 8,9,[19][20][21][22][23] (miktoarm) star, [24][25][26] star block copolymers, 27,28 comb, [29][30][31][32] sun-shaped, [33][34][35] H-shaped, [36][37][38] and θ-shaped 39,40 polymers. Among these nonlinear chain topologies, tadpole-shaped linearcyclic diblock copolymers [41]…”
Section: ' Introductionmentioning
confidence: 99%
“…[1][2][3] It has been well-established that the topological structures and chemical composition of nonlinearshaped block copolymers can exhibit dramatic effects on the solution properties and self-assembling morphologies as compared with their linear counterpart. [4][5][6][7][8][9] It is worthy of noting that the developments of a variety of controlled radical polymerization techniques 10 such as atom transfer radical polymerization (ATRP), [11][12][13] reversible addition-fragmentation chain transfer (RAFT) polymerization, [14][15][16] and nitroxide-mediated polymerization (NMP) 17,18 have facilitated the synthesis of nonlinear-shaped polymers with varying chain architectures such as cyclic, 8,9,[19][20][21][22][23] (miktoarm) star, [24][25][26] star block copolymers, 27,28 comb, [29][30][31][32] sun-shaped, [33][34][35] H-shaped, [36][37][38] and θ-shaped 39,40 polymers. Among these nonlinear chain topologies, tadpole-shaped linearcyclic diblock copolymers [41]…”
Section: ' Introductionmentioning
confidence: 99%
“…In the case of vinyl esters and some vinyl amides, DFT modeling showed that an extra-stabilization of the CACo bond occurred via an intramolecular chelation of the cobalt atom with the carbonyl function of the last monomer unit and is responsible for the good control observed (Scheme 2) [51,64]. This intramolecular chelation is made possible by the flexible geometry of Co(acac) 2 [67,68] that is not possible for cobalt complexes bearing tetradentate ligands with a rigid square-pyramidal geometry (such as cobalt porphyrins) [55,69,70]. Co(acac) 2 is however less efficient for acrylates polymerization as the result of the low stability of the CACo bond of the dormant species [71].…”
Section: Introductionmentioning
confidence: 99%
“…Controlled radical polymerization CRP has become an important tool for the preparation of well-defined polymer materials [1][2][3][4][5][6][7][8][9]. The use of organometallic complexes was a significant step towards the development of CRP of various vinylic monomers [1,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition-metal-mediated living radical polymerization (also called atom transfer radical polymerization, A TRP) ( 6, 7), nitroxide-mediated polymerization (NMRP) (8) and reversible transfer as reversible addition fragmentation transfer (RAFT) (9) allow various tailor-made polymers featuring unique properties in terms of molecular weight, molar mass distribution and chi;tin-end functionality to be synthesized. This provides a powerful tool for protein/peptide biology.…”
Section: Introductionmentioning
confidence: 99%